Effect of reactant gas flow orientation on the current and temperature distribution in self-heating polymer electrolyte fuel cells. (8th February 2021) - Rasha, L.; Cho, J.I.S.; Millichamp, J.; Neville, T.P.; Shearing, P.R.; Brett, D.J.L.
Abstract: Fuel cell polarisation performance is typically reported under controlled/constant temperature conditions, as a sign of robust metrology. However, in practice, fuel cells self-heat as they generate current; which varies the temperature across the polarisation curve and affects performance. More detail regarding the internal cell operation can be gleaned by current and temperature distribution mapping. For the case of an unheated cell, 'self-heating' increases the cell temperature and improves performance, resulting in a 'voltage recovery' and a more homogeneous current and water distribution. For actively heated cells, a reduced current is observed in regions of high temperature and low humidity. The positioning of the gas manifolds also has a decisive impact on performance by affecting the reactant concentration, humidity and water distribution. Counter- and cross-flow orientations in a self-heating cell were studied, with a counter-flow orientation with air flowing with gravity producing the most uniform temperature distribution. Graphical abstract: Image 1 Highlights: Performance should be studied under controlled temperature and self-heating modes. Self-heating in unheated PEFCs increases cell temperature and recovers voltage. Temperature distributions form by uneven current, reactant and water distributions. A uniform temperature distribution could minimise performance degradation over time. Counter-flow with air flow with gravity gives a more even temperature distribution.